Civil society and political participation of education actors. A review - Antonio Juan Colom Cañellas (Universidad de La Rioja, 2020)
Participation in politics depends to a large extent on the decentralization of power into the hands of society, thus following the model of republicanism. In this context, civil society in Spain has been more solidly involved and with better results in educational issues, since it has brought about far-reaching innovations in the formal and non-formal spheres of education. On the other hand, in the relations between schools and families, for different social and legislative reasons, there is a pressing lack of participation, only partially improved by the Associations of Parents of students, in spite of their minimal capacity to influence the most important school issues.